Credit Information Sharing and Credit Risk Reduction in Kenya Commercial Banks (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2016)
Financial Institutions are in the business of mobilizing and lending to borrowers and they assume various kinds of financial risks in the process of mobilizing and lending financial resources.This Theoretical study reviewed the literature to investigate the relationship between credit of information sharing and credit risk reduction in Kenya commercial banks. The literature found that the lending policy is periodically reviewed to reflect the prevailing conditions thus loan characteristics, considers an applicant's bank statements thus borrowers characteristics and the credit collection policy thus lenders characteristics before credit is advanced. The study recommends that banks should incorporate credit information sharing to reduce credit risk.